Linear and stratified sampling-based deep learning models for improving the river streamflow forecasting to mitigate flooding disaster - Afan H.A.; Yafouz A.; Birima A.H.; Ahmed A.N.; Kisi O.; Chaplot B.; El-Shafie A. (Springer Science and Business Media B.V., 2023)
algorithm; flooding; forecasting method; machine learning; river flow; sampling; streamflow; Tigris River